NEP 2020 in Practice : Perspectives on Implementation Challenges - Bagga, Teena; Gupta, Pankaj Kumar; Ola, Md Obaidul; Gilani, Priyanka (Prabandhan: Indian Journal of Management, 2025)
Objective : The purpose of this investigation was to identify issues faced by institutions during the implementation of the 2020 National Education Policy (NEP) and, more specifically, to list a variety of operational issues, such as governance issues, curriculum redesign issues, issues with the current assessment systems, and issues with resources. The study also addressed some larger-scale challenges facing higher education in India (such as the inequality currently existing in different regions of India, the digital divide that exists currently, and the equity and inclusion concerns). Methodology : This investigation utilised a qualitative method. The investigation analyzed both the policy itself and the practical experiences of the implementers. Findings : The findings of the investigation showed that there are many obstacles to implementing the NEP (such as resistance to change; very rigid departmental structures; minimal or no interaction between academia and industry; and poor alignment between the accreditation frameworks utilized to assess quality). Additionally, the study found that institutions experience challenges when it comes to revising curricula, schedules, and developing flexible entry/exit points. Finally, the study identified some universal problems that may hinder an institution’s ability to achieve the transformative vision of the NEP (such as inequity; mental health issues experienced by students and staff; and lack of adequate infrastructure). Originality : The original contribution of this study is represented by the development of a single framework that allowed us to examine the operational, cultural, and systemic challenges that universities face when they implement the NEP. Additionally, the study stressed upon the importance of the commitment required from professors as well as the leadership and the emotional connection as key factors to sustain the reform process, thus providing a holistic approach to apply the NEP and to go beyond the mere technical application of the policy.